Reflections on the discourse of the publicities from private organizations in face of the Brazilian political scene - Carareto, Mariana [UNESP]; Calonego, Renata [UNESP]; Andrelo, Roseane [UNESP] (Coimbra University Press, 2019)
In search of legitimation, companies develop communication strategies appropriating historical and sociocultural contexts to construct meanings about them, as is the case of advertising. This work, when looking at the political situation experienced by Brazil after the political coup against the government of President Dilma Rousseff, aims to reflect on the impacts of political positions disseminated in advertisements, considering that companies have great responsibility in communicating with society. For this, the study develops an analysis of Habib’s and Havan’s advertising campaigns, which disseminate discourses on the Brazilian political context, having as theoretical-methodological foundation the analysis of media discourse proposed by Charaudeau.
Reflexões sobre o discurso das publicidades de organizações privadas diante do cenário político brasileiro
Keywords: Communication; Impacts on society; Political positioning; Private organizations; Responsibility